Development of Small Scale Tape Industry through Composting Its Solid Waste - Suprayogi, Suprayogi; Hidayat, Nur; Santoso, E.F. Sri Maryani; L., Endah Rahayu; Siswanto, Aris (Jurnal Teknologi Pertanian, 2008)
The cassava husk is solid waste of production process of cassava, the cassava husk have big enough potency of amount side. This study aimed to exploit the solid waste of cassava husk become compost, so that can improve economic value of the waste and to know the starter concentration of Aspergillus niger sp and the appropriate time of incubation so that get quality compost of cassava husk, and for the eligibility of small industrial scale cassava husk compostThe process of composting Windrow open system uses starter of Aspergillus niger sp 10, 20 and 30 % with time of incubation during 6, 9, 12, 15, 18, 21, 24, 27, 30 days. Elections of the best treatment pursuant to compost parameter standard show that treatment of K7 that is addition of starter rate 0% with time of incubation 24 days are the best treatment. The best treatment result have rate of C 22.87%, Total N 11.23%, C/N 18.60%, P2O5 0.82%, K2O 0.92%, KA 18.50%, pH 7.05, yield 41.04%, temperature 27 0C and amount of spores 144.543 (x104)/g. From the result analyses eligibility of effort making of competent cassava husk compost to be run calculation of criterion eligibility of effort, mount advantage of investment is competent. Economically asses from waste can mount because can become an valuable product cell.Key words: cassava husk, compost, Aspergillus niger sp